2017
DOI: 10.1016/j.gca.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glacial activity on the weathering of Hf isotopes – Observations from Southwest Greenland

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 92 publications
(9 reference statements)
0
25
0
Order By: Relevance
“…The hydrology and chemistry of the Leverett River during the 2009 melt-season have previously been reported (Bartholomew et al, 2011;Hindshaw et al, 2014;Rickli et al, 2017) and the main results are summarized here. The hydrology was typical for a glacierized catchment with strong seasonal variation.…”
Section: Water Samplesmentioning
confidence: 91%
See 1 more Smart Citation
“…The hydrology and chemistry of the Leverett River during the 2009 melt-season have previously been reported (Bartholomew et al, 2011;Hindshaw et al, 2014;Rickli et al, 2017) and the main results are summarized here. The hydrology was typical for a glacierized catchment with strong seasonal variation.…”
Section: Water Samplesmentioning
confidence: 91%
“…Previous work on water draining the Leverett Glacier, an outlet glacier in the Kangerlussuaq area (Figure 1), used Ca, Sr, Nd, and Hf data of water, rock, and mineral separates to constrain chemical weathering reactions contributing to the dissolved load (Hindshaw et al, 2014;Rickli et al, 2017). Our aim in this study was to analyse mineral separates, bulk rock samples, sediments, and water samples for δ 26 Mg and δ 7 Li in order to test whether the dissolution of silicate minerals previously identified as controlling the dissolved load composition in this catchment were consistent with dissolved δ 26 Mg and δ 7 Li values from this region or whether a carbonate contribution to dissolved δ 26 Mg is indeed required.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
“…The role of hydrology and geology was recently demonstrated at a Canadian glacier where seasonal variations in εNd in a geologically heterogeneous catchment were attributed to the changes in subglacial hydrology (distributed to channelised) which altered where erosion occurred (Clinger et al, 2016). In contrast, glacial catchments with more homogenous lithology have little seasonal variation in εNd (Clinger et al, 2016;Rickli et al, 2017). From this small dataset (this study, Viers et al, 2008;Garçon et al, 2013;Clinger et al, 2016) it would appear that seasonal variations of εNd in suspended sediments are present where rivers drain mixed geology and have a pronounced seasonality to their hydrological cycle.…”
Section: Implications For Nd As a Sediment Source Tracermentioning
confidence: 99%
“…Merschel et al [31] showed Incongruent Hf weathering and the decoupling of the Hf-Nd isotope systems due to the 'zircon effect' is less effective during glacial intervals. Either intense glacial mineral grinding and more congruent weathering [35] or longer water-rock interaction time during glacial intervals are suggested to be the responsible for less pronounced Hf-Nd isotope decoupling [36] in seawater. During non-glacial intervals, however, it was shown that trapping of unradiogenic Hf in zircons accounts for 70% up to 99% of the Hf-Nd decoupling on the continental hinterland to reproduce the seawater array by only weathering and erosion processes [22,27].…”
Section: Hf-nd Decoupling On the Continentsmentioning
confidence: 99%
“…Although some studies suggest that boundary exchange processes between sediment and seawater are plausible mechanisms to explain the radiogenic Hf isotopic composition of seawater [28,65], the sorption and dilution mechanisms behind these processes are not known. Rickli et al [36] postulated that the small offset between dissolved Hf-Nd river data and seawater may (similarly to Nd) be explained by boundary exchange processes.…”
Section: Benthic Flowsmentioning
confidence: 99%